Pengaruh Kontribusi Pajak Hotel dan Pajak Restoran terhadap Pajak Daerah Kota Bandung Tahun 2016-2020 - Salsabila Aulya Rahmah; Dian Imanina Burhany (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
Regional autonomy provides wider authority for regional governments to regulate and manage regional government affairs as well as explore and manage regional revenue sources optimally. The purpose of this study was to examine the effect of the contribution of hotel tax revenue and restaurant tax on Bandung City regional taxes in 2016-2020. The research method in this study is a descriptive research method with a quantitative approach. The research environment was carried out at the Regional Revenue Management Agency (BPPD) of Bandung City. The time horizon of this research is a time series study. The type of data used is documentary data sourced from secondary data. The data analysis methods in this study were descriptive statistical analysis, classical assumption test, and multiple linear regression analysis. The results of the partial test of this study indicate that the hotel tax contribution does not significantly affect the Bandung City local tax, the restaurant tax contribution has a positive partial effect on the Bandung City local tax. Simultaneously, it shows that the contribution of hotel tax and restaurant tax has a simultaneous positive effect on Bandung City local tax.